Browning's Later Poetry, 1871-1889 - Ryals, Clyde de L. (Ithaca, NY : Cornell University Press, 2019)
Maintaining that Browning's later work has been underestimated, Professor Ryals gives close, sophisticated readings of the individual poems, covering each of the published volumes from Balaustion's Adventure through Asolando. He emphasizes the overall structure of a poem and the manner in which themes and ideas are presented. The later Browning is portrayed as "a poet intent upon discovering forms that would give shape and meaning to thought and experience."
Frontmatter -- Contents -- Preface / Ryals, Clyde de L. -- Introduction -- 1. Balaustion's Adventure -- 2. Prince Hohenstiel-Schwangau -- 3. Fifine at the Fair -- 4. Red Cotton Night-Cap Country -- 5. Aristophanes' Apology -- 6. The Inn Album -- 7. Pacchiarotto and Other Poems and The Agamemnon of Aeschylus -- 8. La Saisiaz: The Two Poets of Croisic -- 9. Dramatic Idyls and Jocoseria -- 10. Ferishtah's Fancies -- 11. Parleyings with Certain People of Importance in Their Day -- 12. Asolando -- Conclusion -- Bibliography -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019).
JSTOR
Keywords: Browning, Robert, -- 1812-1889 -- Criticism and interpretation; Browning, Robert, -- 1812-1889; LITERARY CRITICISM -- Poetry; Electronic books; Criticism, interpretation, etc